Sintering of ultrafine undoped SnO2 powder - Leite, E. R.; Cerri, J. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Paskocima, C. A. (Elsevier B.V., 2001)
The sintering process of nanometric undoped SnO2 powder was studied. No macroscopic shrinkage was observed during the sintening process. Grain growth kinetics investigation showed that surface diffusion is the dominant mechanism in the temperature range 500-1300 degreesC. For temperatures higher than 1300 degreesC, high weight loss was measured, suggesting evaporation-condensation as the dominant mass-transport mechanism. Thermogravimetric analysis (TG) and mass spectroscopy studies showed that the surface contamination of the SnO2 particles by chemical species like H2O, OH- and CO2, has a strong influence on the role of mass transport controlled by surface diffusion. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: grain growth; sintering; SnO2; surface diffusion